A formula for calculating 30-item Geriatric Depression Scale (GDS-30) scores from the 15-item version (GDS-15) - Yuge Zhang; Marco Hoozemans; Mirjam Pijnappels; Sjoerd M. Bruijn (Experimental Gerontology, 2023)
The Geriatric Depression Scale with 30 items (GDS-30) and with 15 items (GDS-15) are both valid tools for assessing depression in older adults, but their absolute values are not directly comparable. Here, we used a dataset (n = 431) with GDS-30 scores from a project concerning fall-risk assessment in older adults (FARAO) to develop and validate a formula which can be used to convert GDS-15 scores into GDS-30 scores. We found that the GDS-15 score cannot simply be multiplied by 2 to obtain the GDS-30 scores and that estimations of GDS-30 from GDS-15 are not affected by age, sex and MMSE. Therefore, the optimal formula to estimate the GDS-30 score from the GDS-15 score was: GDS-30_estimated = 1.57 + 1.95 × GDS-15. This formula yielded an estimate of GDS-30 with an explained variance of 79 %, compared to 63 % when GDS-15 was simply multiplied by 2. Researchers that have used the GDS-15 and want to compare their outcomes to other studies that reported only the GDS-30 are advised to use this formula.